(3TQM cJGH SjHhjgs - (3Ydj Hf YjSi Hf Ydj Hf YHO Gddg CHi GdMSf GdQheGfis; (3YeQh Hf YKeGf Hf bfHQ GdMGQKj HGdhdGA, CHh HTQ, GdedbH SjHhjg,J (B180 (3g` s
(3ChdgG (B:s
(3jHJOF gPG GdeLdO heG JQNje QLd ESeg fGLi s
(3BNQgG (B:s
(3jfJgi HBNQ HGH GddaX HGdMQa GdhGMO s
(3dgG fSNI CNQi JMJ Qbe (B86 (3fMhs
(3GdeLdO GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs